A single step seismic optimal design method for damped outrigger structure with BRB. (15th December 2021) - Sun, FeiFei; Yang, Guang; Hu, ZhiBin
Highlights: Proposing a member based single step optimization method for seismic design. Establishing equivalent SDOF system through composite mode. Design method based on reference structure rather than uncontrolled structure. The proposed method is suitable for multiple BRB damped outrigger structure. Abstract: Using the passive control performance curve and the idea of mapping, a single step seismic optimal design method for damped outrigger structure with buckling-restrained brace (BRB) was proposed in this paper. In order to consider the influence of high order modes on earthquake responses, composite modes were used to establish equivalent single-degree-of-freedom (SDOF) system of uncontrolled structure and reference structure. The passive control performance curve based on SDOF reference structure was established through the simplified mapping method. According to the performance point determined on the passive control performance curve, seismic mitigation design based on reference structure was conducted using single step optimization method. The proposed method can accurately and simply determine the parameters of BRB and is quite practical as only the response spectrum analysis is needed. Moreover, it can be used for seismic mitigation design of multiple damped outrigger structure and breaks the limitation of the single outrigger structure. Numerical examples show that the damped outrigger structure designed by this method can achieve the desired performance objectives.